Aerodynamic Performance of a Single-stage Transonic Axial Compressor using Recirculation-Bleeding Channels - Vuong, Tien-Dung; Dinh, Duc-Manh; Dinh, Cong-Truong; Bui, Xuan-Long (Old Journal, 2019)
This paper investigates the recirculation channel with an addition of bleeding channels located on shroud surface of recirculation channel in the rotor domain, where the bleeding system consists of 36 channels distributed on the recirculation channel. This study focuses on its effects on aerodynamic performance of a single-stage transonic axial compressor, NASA Stage 37. Validation of numerical results was performed using experimental data for a single-stage transonic axial compressor. A parametric study with only three position of the bleeding channels were performed in a single-stage transonic axial compressor, NASA Stage 37. The numerical results showed the aerodynamic performance of a single-stage transonic axial compressor was increased, such as total pressure ratio, adiabatic efficiency, stall margin as compared to the smooth casing.